Enhancing the Quality of Education through Modern Pedagogical Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the role of modern pedagogical technologies in enhancing the quality of education across secondary and higher educational institutions. While previous research has emphasized the benefits of digital tools in promoting active learning, there remains a gap in understanding their localized implementation, especially in resource-constrained environments. To address this, a mixed-methods approach was employed, combining classroom observations, teacher interviews, and student surveys to examine both teaching practices and student performance.Findings reveal a strong positive correlation between the frequency of technology use and improvements in student engagement and academic outcomes. Teachers reported greater instructional flexibility and learner participation, particularly when using interactive platforms and project-based digital tools. However, challenges such as limited digital literacy and insufficient infrastructure hinder effective integration.The results suggest that modern pedagogical technologies, when thoughtfully implemented and supported by institutional strategies, can significantly improve the quality of education. These findings offer valuable implications for educators and policymakers aiming to modernize educational practices in diverse learning contexts.